2006
DOI: 10.1007/bf02893621
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to volunteer: The role of altruism

Abstract: Volunteering, volunteers, altruism, nonprofit organizations,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 36 publications
6
61
0
4
Order By: Relevance
“…Often altruism is at the centre of volunteer motivations research, and has sparked controversy both for and against (Trogdon 2005). Altruism is a primary impetus for voluntary behaviour (Soupourmas and Ironmonger 2002;Burns et al 2006Burns et al , 2008 and concern with others characterizes this category.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Often altruism is at the centre of volunteer motivations research, and has sparked controversy both for and against (Trogdon 2005). Altruism is a primary impetus for voluntary behaviour (Soupourmas and Ironmonger 2002;Burns et al 2006Burns et al , 2008 and concern with others characterizes this category.…”
Section: Resultsmentioning
confidence: 99%
“…Theories on volunteer motives have been a central point in recent research, although additional research is required to identify primary reasons and motives for volunteering (Burns et al 2006;Briggs et al 2010). According to Esmond and Dunlop (2004) the first research in volunteer work appeared in the seventies, and altruism was one of the first motives identified (Tapp and Spanier 1973).…”
Section: Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By asking participants to rate the distress felt for the person being interviewed, Batson et al (1997) found that imagining how a person in need felt evoked relatively pure empathic emotion, which suggested altruistic motivation to help another person. Likewise, Burns et al (2006) suggested that altruism appeared to be a strong motivator of volunteerism among young people.…”
Section: Conceptual Backgroundmentioning
confidence: 97%
“…The general motivation to volunteer has been investigated in several studies. These studies showed that people volunteer because of altruistic or egoistic motives, e.g., helping others or achieving goals (Cnaan and Goldberg-Glen 1991;Clary et al 1996;Thoits and Hewitt 2001;Peterson 2004;Burns et al 2006;Pajo and Lee 2011;Ferreira et al 2012;Do Paço et al 2013;Vázquez et al 2015). Further motives included personal dispositions, such as empathy or prosocial attitudes (Clary et al 1998;Davis et al 1999;Penner 2002;Hustinx and Lammertyn 2003;Peloza and Hassay 2006).…”
Section: Literature Reviewmentioning
confidence: 99%